Comparison of central vein pressure between distal, medial, and proximal lumens with water manometer method - Cornellius Hendra Purnama Aria Sumantrie; Bambang Pujo Semedi; Bambang Purwanto (Qanun Medika - Jurnal Kedokteran FK UMSurabaya, 2021)
ABSTRACT Catheter Vein Pressure in ward-cared patients is rarely measured and considered invalid. The two catheter vein pressure postulates contradict, making confusion among health workers. Dr Russo said the distal-medial-proximal Catheter Vein Pressure has no difference but were denied by Susan S. Scott. Proof of postulate is needed as a solution to inward care. Therefore, this study aimed to compare the central vein pressure between distal, medial, and proximal lumens with the water manometer method. Forty-nine samples retrospective study were taken from the distal - medial - proximal Catheter Vein Pressure of the "zero" until fifth days. The differences are analyzed with Statistical Paired t Test with p-Value < 0.05 from SPSS ver. 26 to prove the right postulate. 49 samples were concluded to represent of population. Catheter Vein Pressure from day "zero" becomes zero difference, the fifth day 91.8% are no difference while the rest have difference of 0.2 - 1.0 cm H2O and the conclusion are no significant difference with 95% CI. The correlation scale of 0.998 and 0.999 proves that the three lumens tend to produce no differences. In conclusion, the distal - medial - proximal Catheter Vein Pressure values in this study have no significant differences and consistent from "zero" until fifth days. This is formulated as P distal = P medial = P proximal (cm H2O).Keywords      : Central Vein Pressure, Pressure, distal - medial - proximal, no differences, ward patient.Correspondence    : sumantrie_medicalgp@yahoo.com